Principles of marketing - Kotler, Philip; Armstrong, Gary (Upper Saddle River Prentice Hall, 2001)
Contents: understanding marketing and the marketing process; developing marketing opportunities and strategies; developing the marketing mix; managing marketing.
Includes bibliographical references and index
Keywords: Quản trị kinh doanh